Cable-Piliated Burkholderia cepacia Binds to Cytokeratin 13 of Epithelial Cells - Sajjan, Umadevi S. (American Society for Microbiology, 2000)
Although the Burkholderia cepacia complex consists of several genomovars, one highly transmissible strain of B. cepacia has been isolated from the sputa of cystic fibrosis (CF) patients throughout the United Kingdom and Canada. This strain expresses surface cable (Cbl) pili and is thought to be the major strain associated with the fatal “cepacia syndrome.” In the present report we characterize the specific 55-kDa buccal epithelial cell (BEC) protein that binds cable pilus-positive B. cepacia. N-terminal sequences of CNBr-generated internal peptides identified the protein as cytokeratin 13 (CK13). Western blots of BEC extracts probed with a specific monoclonal antibody to CK13 confirmed the identification. Mixed epidermal cytokeratins (which contain CK13), cytokeratin extract from BEC (which consists essentially of CK13 and CK4), and a polyclonal antibody to mixed cytokeratins inhibited B. cepacia binding to CK13 blots and to normal human bronchial epithelial (NHBE) cells. Preabsorption of the antikeratin antibody with the BEC cytokeratin fraction reversed the inhibitory effect of the antibody. A cytokeratin mixture lacking CK13 was ineffective as an inhibitor of binding. Colocalization of CK13 and B. cepacia by confocal microscopy demonstrated that intact nonpermeabilized NHBE cells express small amounts of surface CK13 and bind Cbl-positive B. cepacia in the same location. Binding to intact NHBE cells was dependent on bacterial concentration and was saturable, whereas a Cbl-negative isolate exhibited negligible binding. These findings raise the possibility that surface-accessible CK13 in respiratory epithelia may be a biologically relevant target for the binding of cable piliated B. cepacia.